Assessing the efficiency of government budget expenditure across provinces in Thailand - Chollagran, Sukhumal; Pasunon, Prasopchai; Lateh, Afifi (Edelweiss Applied Science and Technology, 2025)
This research aims to: 1) identify input and output factors for evaluating the efficiency of government budget spending in the spatial dimension of provinces in Thailand, and 2) evaluate the efficiency of government budget spending in the spatial dimension of 76 provinces in Thailand, excluding Bangkok. A mixed-method approach was employed, combining qualitative and quantitative research. The qualitative study involved in-depth interviews with 20 key informants to determine input, output, and environmental factors. The quantitative analysis utilized the Data Envelopment Analysis method, applying both the CCR and BCC models to evaluate efficiency scores. The research results revealed: 1) The input factors consist of total budget expenditure and total budget expenditure per capita. The output factors include provincial gross product, proportion of poor people, coefficient of income inequality, employment rate, and crime cases. The environmental factors encompass population density, average years of education, and unemployment rate. 2) Based on the model utilizing the input factors and the output factors, the evaluation of government budget spending efficiency in 76 provinces (excluding Bangkok) found that the CCR model had an average efficiency score of 0.567, the BCC model had an average efficiency score of 0.619, and the SE model had an average efficiency score of 0.932.